2009
DOI: 10.1308/003588409x391758
|View full text |Cite
|
Sign up to set email alerts
|

Testing the feasibility of intra-operative sentinel lymph node touch imprint cytology

Abstract: Intra-operative sentinel lymph node assessment using touch imprint cytology is feasible within a busy NHS practice. We now offer touch imprint cytology to patients following appropriate counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, touch imprint cytology sensitivity is dependent on the burden of disease on a bivalved lymph node. 33 Therefore, micrometastatic disease can easily be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, touch imprint cytology sensitivity is dependent on the burden of disease on a bivalved lymph node. 33 Therefore, micrometastatic disease can easily be missed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Asthana et al, the average time taken for reporting the IC for lymph nodal metastasis in head and neck cancer was 15 minutes 3 . Jahromi et al assessed the feasibility of sentinel lymph node using Touch IC in carcinoma breast 20 . The average time for reporting in this study was 25.7 ± 6.4 minutes.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, non‐ductal histological subtype and the absence of lymphovascular invasion were identified as significant independent factors associated with a higher FNR. Wide ranges of sensitivity (34–96.9%) and specificity (96.3–100%) have been reported for cytological techniques . A meta‐analysis of 31 studies of IC identified an overall sensitivity of 63%, and the pooled sensitivity for detection of macrometastases was higher than for micrometastases (81% versus 22%) .…”
Section: Intraoperative Evaluation (Ioe) Of Slnsmentioning
confidence: 99%